Legal Review Of The Debtor's Obligation To Settle Debts Even Though The Fiducia Collateral Has Been Returned: Study of Decision Number 300/Pdt.G/2024/PN.Btm - Josua Daniel Pedrosa Simatupang; Yanti Agustina (Lembaga Penelitian dan Pendidikan (LPP) Mandala, 2026)
This study aims to examine the legal obligation of debtors to repay their debts after the fiduciary collateral object has been returned to the creditor, as well as to analyze the forms of legal protection that can be provided to debtors within fiduciary agreements. In addition, this research also analyzes the legal considerations of judges in the Decision of the Batam District Court Number 300/Pdt.G/2024/PN Btm concerning fiduciary security disputes. This research employs a normative legal research method using both statutory and case approaches. The legal materials consist of primary, secondary, and tertiary sources obtained through library research. The collected materials are analyzed qualitatively using a descriptive-analytical method, and conclusions are drawn through a deductive approach. The results indicate that the return of the fiduciary collateral object does not automatically eliminate the debtor’s obligation to repay the outstanding debt, as stipulated under Law Number 42 of 1999 concerning Fiduciary Security. However, in practice, there is often an imbalance of position between debtors and creditors, particularly in the execution process, which tends to lack transparency and may disadvantage the debtor. Therefore, stronger legal protection is required for debtors, especially in relation to the valuation and sale of the collateral object. The analysis of the court decision shows that the judge’s considerations tend to emphasize formal legal certainty, and have not fully reflected the principles of justice and legal protection for debtors.